PEMBERDAYAAN BADAN USAHA MILIK DESA DALAM MENINGATKAN USAHA DAN EKONOMI MASYARAKAT DENGAN PENDEKATAN KELOMPOK DESA JABON KECAMATAN KALIDAWIR KABUPATEN TULUNGAGUNG - Siswahyudianto Siswahyudianto (As-Sidanah, 2020)
Establishment "BUMDes is also intended to encourage, facilitate, protect and empower economic activities in rural areas that are based on potential" villages or activities both" develop according to the customs and culture of the local community. Village economic institutional strengthening is ultimately intended to improve the socio-economic welfare of rural communities and support the optimization of poverty alleviation programs. The vision of BUMDes "Mekar Jaya" is to realize the welfare of the people of Jabon Village through the development of economic businesses and social services, with the motto, let's build the village together. Based on village deliberations, the village empowerment program concentrates on agriculture, fisheries and computer technology for entrepreneurs.